METHODS OF FINANCIAL ANALYSIS OF THE RESULTS OF THE ACTIVITIES OF ECONOMIC ENTITIES - Babadjanov Abdirashid Musayevich (Western European Studies, 2024)
This article will consider the results of the activities of economic entities and reveal methods of their financial analysis. One of the most important conditions for the successful management of the finances of business entities is the analysis of its financial condition. It is characterized by the availability of financial resources necessary for the normal functioning of business entities, their correct placement and effective use, financial relations with other legal entities and individuals, solvency and financial stability.
Keywords: financial; effective; conditions